THE ROLE OF PDGF AND TSP-1 IN THE DEVELOPMENT OF SYSTEMIC SCLERODERMA (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Systemic scleroderma (SSc), also called systemic sclerosis, is a chronic autoimmune disease. It causes: - Thickening and hardening of the skin - Damage to small blood vessels - Fibrosis of internal organs (like lungs, heart, kidneys)